A Model in the Planning of Standart Nursing Care of a Case Rectal Cancer : "Functional Health Patterns” - Gürler, Hesna; Yılmaz, Meryem (Fırat University, 2011)
Colorectal cancer is increasing significantly in the world. In 2006, colorectal cancer is the third most common cancer affecting about one million cases and resulting in death more than 500,000. Patient aged 51 entered to hospital because of rectal bleeding. after rectal examination, colonoscopy and biopsy, it was determined that there was a malignant epithelial tumor that. was 3 cm length and obstruct the lumen. Patient was hospitalized to a Surgery clinic for surgery and the permanent colostomy was opened by rectosigmoid resection. The case had evaluated using a the standard form that was prepeared with “functional health patterns" model that was developed in 1982 by Gordon and then standard nursing initiatives had planned.

Kolorektal kanser, dünyada anlamlı şekilde artmaktadır. 2006 yılında yaklaşık bir milyon vakayı etkileyen ve 500.000'den fazla ölümle sonuçlanan üçüncü en yaygın kanserdir. Olguda 51 yaşındaki erkek hasta rektal kanama nedeniyle hastaneye başvurmuştur. Yapılan rektal muayene, kolonoskopi ve biyopsi sonucunda 3 cm uzunluğunda lümeni tıkayan malign epitelyal tümör belirlenmiştir. Hasta cerrahi kliniğine yatırılarak rektosigmoid rezeksiyon yapılmış ve kalıcı kolostomi açılmıştır. Olgu 1982'de Gordon tarafından geliştirilmiş “Fonksiyonel Sağlık Örüntüleri (FSÖ)” modeli kullanılarak hazırlanmış standart bir form kullanılarak değerlendirilmiş ve standart hemşirelik girişimleri planlanmıştır.
Rektum Kanserli Bir Olgunun Standart Hemşirelik Bakımının Planlanmasında Bir Model: “Fonksiyonel Sağlık Örüntüleri''